Modeling the effects of process conditions on the accumulated lethality values of thermally processed pickled carrots - Acosta Montoya, Óscar Gerardo (2015)
Shelf-stable pickled products are thermally processed to ensure safety and stability. Carrots packed in glass jars and processed in a boiling water bath were chosen to construct models to predict accumulated lethality values given process conditions and heating times. Mixed models with a natural logarithmic transformation of accumulated lethality as response showed that the effect of blanching prior to filling did not significantly impact the response (P > 0.05), while the effects of ln process time, jar size, carrots to brine ratio, carrot spear diameter, brine temperature, and concentration of sucrose in the brine and interactions among these variables significantly affected the response (P < 0.001), as evaluated in different experimental designs. The residual unexplained replicate-to-replicate variability of all constructed models was always <3% and every trial was conducted in triplicate. Process authorities can use these models to establish processing guidelines or evaluate current processes for production of shelf-stable pickled carrots or similar foods (as demonstrated by the validation experiments) with pH values from <3.9 to 4.4. This study also demonstrated that it is feasible to use this experimental setup to evaluate the impact of changes in processing conditions on the accumulated lethality values reached through thermal processing of similar foods. Overall, these results contribute to the establishment of science-based processing guidelines that will ensure production of safe and stable products with optimized heating times to enhance quality parameters.